Rapid Selective Detection of Potentially Infectious Porcine Epidemic Diarrhea Coronavirus Exposed to Heat Treatments Using Viability RT-qPCR - Puente, Héctor; Randazzo, Walter; Falcó, Irene; Carvajal, Ana; Sánchez, Gloria (Frontiers in Microbiology, 2020)
Coronaviruses (CoVs) cause severe respiratory, enteric and systemic infections in a wide range of hosts, including humans and animals. Porcine epidemic diarrhea virus (PEDV), a member of the Coronaviridae family, is the etiological agent of porcine epidemic diarrhea (PED), a highly contagious intestinal disease affecting pigs of all ages. In this study, we optimized a viability RT-qPCR for the selective detection of infectious and heat-inactivated PEDV. PEMAX™, EMA™, and PMAxx™ photoactivable dyes along with PtCl4 and CDDP platinum compounds were screened as viability markers using two RT-qPCR assays: firstly, on PEDV purified RNA, and secondly on infectious and thermally inactivated virus suspensions. Furthermore, PMAxx™ pretreatment matched the thermal inactivation pattern obtained by cell culture better than other viability markers. Finally, we further optimized the pretreatment by coupling viability markers with Triton X-100 in inoculated serum resulting in a better estimation of PEDV infectivity than RT-qPCR alone. Our study has provided a rapid analytical tool based on viability RT-qPCR to infer PEDV infectivity with potential application for feed and feed ingredients monitoring in swine industry. This development would allow for greater accuracy in epidemiological surveys and outbreak investigations.